Improved identification of severely injured pediatric trauma patients using reverse shock index multiplied by Glasgow Coma Scale. Issue 1 (January 2022) - Reppucci, Marina L.; Acker, Shannon N.; Cooper, Emily; Meier, Maxene; Stevens, Jenny; Phillips, Ryan; Moulton, Steven L.; Bensard, Denis D.
Abstract : BACKGROUND: The shock index pediatric age-adjusted (SIPA) predicts the need for increased resources and mortality among pediatric trauma patients without incorporating neurological status. A new scoring tool, rSIG, which is the reverse shock index (rSI) multiplied by the Glasgow Coma Scale (GCS), has been proven superior at predicting outcomes in adult trauma patients and mortality in pediatric patients compared with traditional scoring systems. We sought to compare the accuracy of rSIG to Shock Index (SI) and SIPA in predicting the need for early interventions in civilian pediatric trauma patients. METHODS: Patients (aged 1–18 years) in the 2014 to 2018 Pediatric Trauma Quality Improvement Program database with complete heart rate, systolic blood pressure, and total GCS were included. Optimal cut points of rSIG were calculated for predicting blood transfusion within 4 hours, intubation, intracranial pressure monitoring, and intensive care unit admission. From the optimal thresholds, sensitivity, specificity, and area under the curve were calculated from receiver operating characteristics analyses to predict each outcome and compared with SI and SIPA. RESULTS: A total of 604, 931 patients with a mean age of 11.1 years old were included. A minority of patients had a penetrating injury mechanism (5.6%) and the mean Injury Severity Score was 7.6. The mean SI and rSIG scores were 0.85 and 18.6, respectively. Reverse shock index multiplied by Glasgow Coma Scale performed better than SI and SIPA at predicting early trauma outcomes for the overall population, regardless of age. CONCLUSION: Reverse shock index multiplied by Glasgow Coma Scale outperformed SI and SIPA in the early identification of traumatically injured children at risk for early interventions, such as blood transfusion within 4 hours, intubation, intracranial pressure monitoring, and intensive care unit admission. Reverse shock index multiplied by Glasgow Coma Scale adds neurological status in initial patient assessment and may be used as a bedside triage tool to rapidly identify pediatric patients who will likely require early intervention and higher levels of care. LEVEL OF EVIDENCE: Prognostic, level III. Abstract : The novel scoring tool, reverse shock index times Glasgow Coma Scale (rSIG), proves superior to both SI and SIPA at identifying traumatically injured children at risk for early interventions.